2019
DOI: 10.1186/s13045-019-0783-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and death in 29 cancer groups in 2017 and trend analysis from 1990 to 2017 from the Global Burden of Disease Study

Abstract: Background and aims Cancer has become the second most serious disease threatening human health, followed by cardiovascular diseases. This study aimed to quantitatively estimate the mortality, morbidity, and analyze the trends of 29 cancer groups in 195 countries/regions between 1990 and 2017. Methods Detailed information of 29 cancer groups were collected from the Global Burden of Disease (GBD) study in 2017 and age-standardized inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
104
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(109 citation statements)
references
References 46 publications
0
104
0
5
Order By: Relevance
“…The apparent improvement in the survival of CML patients mainly occurred in high-income countries like the United States, France, and Japan [ 9 11 ]. The disease burden of CML distinctly varies in different countries due to diverse opportunities for early-stage screening, novel drugs and medical resources [ 12 , 13 ]. The worldwide disease burden of CML is worth evaluating, which can help us better understand the specific impact of this disease on public health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent improvement in the survival of CML patients mainly occurred in high-income countries like the United States, France, and Japan [ 9 11 ]. The disease burden of CML distinctly varies in different countries due to diverse opportunities for early-stage screening, novel drugs and medical resources [ 12 , 13 ]. The worldwide disease burden of CML is worth evaluating, which can help us better understand the specific impact of this disease on public health.…”
Section: Introductionmentioning
confidence: 99%
“…The Global Burden of Disease (GBD) study 2017 contains epidemiologic data about 354 diseases across 195 countries and territories, providing an opportunity to understand the worldwide trends in the disease burden of CML [ 13 ]. Accordingly, we described the incidence, deaths, disability-adjusted life-years (DALYs), and its attributable risk factors of CML by age, sex, geographical regions, social-development index (SDI) on specific CML data from the (GBD) study 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The global burden of cancer is rapidly increasing, and established risk factors for cancer include smoking, poor diet, overweight, and physical inactivity. 1,2 The burden of cancers is expected to be further increased by increases in these risk factors, particularly in less developed countries. 3,4 TheGBD study reported that the global burden of childhood cancers mainly existed in developing countries in 2017, 5 and there are age and gender differences in the global trends of incidence and death for specific cancers.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous papers we reported the original rearrangement of spiro-fused pyrimidines and 1,3-benzoxazines into acridines and benzoxanthenes, respectively [48][49][50][51]. We found that treatment of spiro thienopyrimidine 3a with an excess of Vilsmeier-Haack reagent for 4 days at room temperature afforded 1-cyclohex-1-en-1-yl-5,6,7,8-tetrahydro [1]benzothieno[2,3-d]pyrimidin-4(1H)one 10 in a moderate yield. The same rear-rangement product was isolated when the reagents were heated at 100-110ºС for 3 h (Scheme 3).…”
Section: Resultsmentioning
confidence: 98%
“…Over the past few decades, the survival of cancer patients has improved significantly due to the progress in early detection and treatment [1].…”
Section: Introductionmentioning
confidence: 99%